Reducing Submodule Capacitance for Modular Multilevel Converter-Based Medium-Voltage Wind Power Converter - Qian, Jianhang; Liu, Zhijie; Li, Ke-Jun; Li, Liangzi; Guo, ZhongLin (Frontiers in Energy Research, 2022)
This study presents a strategy to reduce the capacitance of the submodule (SM) capacitor of a modular multilevel converter-based medium-voltage wind power converter. The design of the SM capacitor of the modular multilevel converter (MMC) should consider the actual operating conditions, especially the influence of wind speed, because wind speed will affect the voltage ripple and voltage amplitude of the SM capacitor. In the traditional method, the capacitance design of the SM capacitor will be based on relatively high wind speed and leave a certain safety margin. However, in most cases, the system operates at the highest-frequency wind speed (HFWS). For the MMC-based wind energy conversion system, a constant capacitor voltage ripple (CCVR) control method is proposed. Using this method, the SM capacitor voltage ripple can be significantly reduced by injecting the second harmonic component of circulating current. In this way, the SM capacitor with smaller capacitance can be used. Finally, the effectiveness of the proposed method is validated in RT-Lab Platform.